Data Visualization Using Google Data Studio: A Case Study of the 2019 Presidential Indonesia Election Results - Bangkit Habiburrohman; Yanto, Budi; Muhammad Arif (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The 2019 Indonesian Presidential Election generated a significant amount of data requiring effective visualization for analysis and comprehension. This study demonstrates the application of Google Data Studio, a data visualization tool, for creating interactive dashboards based on election results. The dataset was sourced from the official Bureau of Statistics and processed to produce visualizations such as scorecards, bar charts, and pie charts, facilitating detailed insights into regional and candidate-specific voting patterns. The methodology includes data collection, processing, and visualization to construct a comprehensive dashboard. The findings illustrate the potential of Google Data Studio in enhancing data interpretability and decision-making through interactive visual representations. This research provides a practical guide for leveraging Google Data Studio in electoral data analysis